Prototype Testing of a New Passive Energy Dissipation Device for Seismic Retrofit of Bridges - Shaban, Nefize; Caner, Alp (Frontiers in Built Environment, 2016)
The increasingly demanding performance requirements trigger the development of new devices to eliminate the limitations concerning the post-earthquake performance of available seismic protection systems. The prerequisite for economical earthquake-resistant bridges is the structures’ capacity to absorb and dissipate a large amount of seismic energy. A widely considered strategy for enhancing this capacity is through the use of passive energy dissipation systems for seismic protection of structures. It has been known that majority of the available energy dissipation systems are non-usable after a major earthquake, which increases the risk of collapse during an aftershock. The focus of the current study is given to introduce a new type of passive energy dissipation device with a pending patent that is testified to have an improved energy dissipation capacity without suffering any damage while absorbing energy. Thus, the proposed damper does not require an immediate expensive replacement and keeps its operational capabilities and effectiveness during aftershocks. The paper presents the dynamic performance tests of the first full-scale prototype of the damper that eventually prove it to be a promising design with an improved energy dissipation capacity and stable behavior during and after the dynamic event.